2020
DOI: 10.21203/rs.3.rs-88933/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dichloroacetate and PX-478 Exhibit Strong Synergistic Effects in a Various Number of Cancer Cell Lines.

Abstract: Background: One key approach for anticancer therapy is drug combination. Drug combinations can help reduce doses and thereby decrease side effects. Further, the likelihood of drug resistance is reduced. Distinct alterations in tumour metabolism have been described in past decades, but metabolism has yet to be targeted in clinical cancer therapy. Recently, we found evidence for a synergism between dichloroacetate (DCA), a pyruvate dehydrogenase kinase inhibitor and HIF1-α inhibitor PX-478. In this study, we aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…The increased activity of glycolytic genes and enzymes in tumors represents an important resistance factor against apoptosis [446]. DCA anti-tumor effects are significantly increased when used in association with PX-478, a HIF-1α inhibitor [447].…”
Section: Discussionmentioning
confidence: 99%
“…The increased activity of glycolytic genes and enzymes in tumors represents an important resistance factor against apoptosis [446]. DCA anti-tumor effects are significantly increased when used in association with PX-478, a HIF-1α inhibitor [447].…”
Section: Discussionmentioning
confidence: 99%
“…HIF inhibitors are an important type of hypoxia targeted therapy drugs and a large number of studies have shown that HIF inhibitors (such as PX-478, LW6), either as a single agent or in combination with other therapeutic agents, exhibited promising anti-tumor effects. 81- 84…”
Section: Potential Treatment Exploiting Tumor Hypoxiamentioning
confidence: 99%